Performance implication of management accounting systems in market-oriented firms: Empirical evidence from Vietnam - Bui Quang Hung; Tu Thanh Hoai; Tran Anh Hoa; Nguyen Phong Nguyen (Cogent Business & Management, 2023)
AbstractDrawing upon the resource-based view, this study examines the effects of two key elements of market orientation, i.e. customer orientation and competitor orientation, on the use of management accounting information to enhance firm performance. The partial least squares structural equation modeling (PLS-SEM) results from data collected from top- and mid-level managers working in 279 large companies in Vietnam indicate both customer and competitor orientation have positive effects on the use of management accounting systems (in terms of broad scope, timeliness, aggregation, and integration). This, in turn, enhances firm performance. The study’s results provide various theoretical and managerial implications for building and developing management accounting systems for Vietnamese companies.